SALMA: An Efficient State-Based Hybrid Routing Protocol for Mobile Nodes in Wireless Sensor Networks. (21st February 2016) - Umar, Muhammad Muneer; Alrajeh, Nabil; Mehmood, Amjad
With the rapid development in mobile Wireless Sensor Networks (WSNs), it has become very essential to focus on the efficiency in performance of small sensing nodes operating in WSNs. While designing a routing protocol for mobile sensor nodes, the quality parameters like end-to-end delays and routing overhead are always considered. Moreover, the nodes in wirelessly connected mobile networks consume considerable power on routing more than other functionalities. Any modification in a standard routing protocol can also affect routing overhead, end-to-end delays, and energy consumption of nodes. In this paper a new hybrid routing protocol, named as State-Aware Link Maintenance Approach (SALMA), is introduced which is based on Dynamic Source Routing (DSR) and Optimized Link State Routing (OLSR) protocols. The work also focuses on the activeness of nodes in the network operations and defines three states of nodes, that is, white, gray, and black. The work concludes that the proposed protocol gives improvements in some quality of service metrics like lower delay than DSR, lower routing overhead than OLSR, and lesser energy consumption by the network nodes.